Analysis on the effects of wallstreetbets on the stock market - Hossain, Abir; Sarker, Zahid; Radib, Md Sadman; Taher, Sayed Bin; Samrat, Syed Mohebbullah (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.